Inactivation of Pepper Mild Mottle Virus in Water by Cold Atmospheric Plasma - Filipić, Arijana; Dobnik, David; Tušek Žnidarič, Magda; Žegura, Bojana; Štern, Alja; Primc, Gregor; Mozetič, Miran; Ravnikar, Maja; Žel, Jana; Gutierrez Aguirre, Ion (Frontiers in Microbiology, 2021)
Water scarcity is one of the greatest threats for human survival and quality of life, and this is increasingly contributing to the risk of human, animal and plant infections due to waterborne viruses. Viruses are transmitted through polluted water, where they can survive and cause infections even at low concentrations. Plant viruses from the genus Tobamovirus are highly mechanically transmissible, and cause considerable damage to important crops, such as tomato. The release of infective tobamoviruses into environmental waters has been reported, with the consequent risk for arid regions, where these waters are used for irrigation. Virus inactivation in water is thus very important and cold atmospheric plasma (CAP) is emerging in this field as an efficient, safe, and sustainable alternative to classic waterborne virus inactivation methods. In the present study we evaluated CAP-mediated inactivation of pepper mild mottle virus (PMMoV) in water samples. PMMoV is a very resilient water-transmissible tobamovirus that can survive transit through the human digestive tract. Furthermore, its inactivation using various water-treatment methods is similar to or lower than enteric virus inactivation. For these reasons, PMMoV can be used as an indicator for fecal water pollution and as a surrogate for enteric viruses. The efficiency of PMMoV inactivation was characterized for infectivity and virion integrity, and at the genome level, using test plant infectivity assays, transmission electron microscopy, and molecular methods, respectively. Additionally, the safety of CAP treatment was determined by testing the cytotoxic and genotoxic properties of CAP-treated water on the HepG2 cell line. Five-minute treatment with CAP was sufficient to inactivate PMMoV without introducing any cytotoxic or genotoxic effects in the in-vitro cell model system. These data on inactivation of such stable waterborne virus, PMMoV, will encourage further examination of CAP as an alternative for treatment of potable and irrigation waters, and even for other water sources, with emphasis on inactivation of human, animal and plant pathogenic viruses.